Research in personnel and human resources management. Vol. 23 - Martocchio, Joseph J. (Research in personnel and human resources management,, 2004)
This series, publishes monograph length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 23 of "Research in Personnel and Human Resources Management" (RPHRM) contains eight papers on critical issues in the field of human resources management, thus continuing the tradition of the series to develop a more informed understanding of the field.These include: Fairness in Idiosyncratic Work Arrangements - Justice as an I-Deal Sexual Orientation in the Workplace; The Unique Work and Career Experiences of Gay, Lesbian and Bisexual Workers; Organizational Staffing - A Multilevel Review, Synthesis and Model; The Four-Fifths Rule for Assessing Adverse Impact - An Arithmetic, Intuitive, and Logical Analysis of the Rule and Implications for Future Research; Going Places - Roads More or Less Travelled in Research on Expatriate Experiences; Inference Problems with Hierarchical Multiple Regression-Based Tests of Mediating Effects; and, The Employee Organization Relationship - A Timely Concept in a Period of Transition.